2023
DOI: 10.1002/aoc.7174
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the anticancer potential of thiadiazole derivatives of substituted thiosemicarbazones formed via copper‐mediated cyclization

Abstract: A couple of N‐(4)‐morpholine/pyrrolidine‐substituted thiosemicarbazones (TSCs) of fluorene‐2‐carboxaldehyde (FM and FP), and their corresponding thiadiazoles (TDZs) (CFM and CFP), were synthesized and characterized (elemental analysis, ultraviolet–visible [UV–Visible], Fourier transform infrared [FT‐IR], nuclear magnetic resonance [NMR; 1H & 13C], high‐resolution mass spectrometry [HRMS], and single‐crystal X‐ray diffraction [SCXRD]) for the evaluation of their anticancer potential. The TDZs were obtained unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Ru-arene complexes, cisplatin, NAMI-A, and KP1019 were tested for cytotoxicity using MTT assay against MCF-10a normal breast cells and human breast cancer (MDA-MB-231), lung cancer (A459), and cervical cancer (HeLa) cell lines. 30 The experimental protocol is described in depth in the appendices (Section S10).…”
Section: Density Functional Theory (Dft) Studymentioning
confidence: 79%
“…Ru-arene complexes, cisplatin, NAMI-A, and KP1019 were tested for cytotoxicity using MTT assay against MCF-10a normal breast cells and human breast cancer (MDA-MB-231), lung cancer (A459), and cervical cancer (HeLa) cell lines. 30 The experimental protocol is described in depth in the appendices (Section S10).…”
Section: Density Functional Theory (Dft) Studymentioning
confidence: 79%
“…The molecular electrostatic potential (MEP) surface of RuPCAM , in addition to all other complexes, is depicted in Figure . The electron density is primarily concentrated around the sulfur atom and the five-membered ring formed during coordination (with the color red denotes areas rich in electrons, the color blue denotes areas low in electrons, and green denotes the neutral area) . This means that the complexes’ sulfur and five-membered ring are likely to interact strongly with biomolecules like proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this induced planarity of S13−C12−N11−N10 in RuPCAM could also enhance the ligand to metal charge transfer (LMCT), 44 which is very evident in the absorption spectra of RuPCAM (see supplementary the sulfur atom and the five-membered ring formed during coordination (with the color red denotes areas rich in electrons, the color blue denotes areas low in electrons, and green denotes the neutral area). 45 This means that the complexes' sulfur and five-membered ring are likely to interact strongly with biomolecules like proteins.…”
Section: Molecular Structure Analysismentioning
confidence: 99%
“…Due to the presence of the N–C–S moiety, 1,3,4-thiadiazole derivatives are thought to have different biological activities . Authors recommend that the 1,3,4-thiadiazole derivative’s biological activities are shown due to the strong aromaticity of the ring, in vivo stability, and thiadiazole had less to zero toxicity for higher vertebrates, which includes humans for the treatment of cancer. , The aromatic five-membered ring of thiadiazole contains two nitrogen atoms and one sulfur atom. It also has a two-electron donor system and a hydrogen bonding domain, allowing it to act as an anhydrase …”
Section: Introductionmentioning
confidence: 99%